PENGARUH KOMBINASI RANGE OF MOTION (ROM) DAN KOMPRES HANGAT TERHADAP PENINGKATAN KEMAMPUAN ACTIVITY DAILY LIVING PADA PASIEN PASCA STROKE DI WILAYAH KERJA PUSKESMAS KECAMATAN LIMO DEPOK - Nur Rohmah, (2022)
Stroke can cause decreased ability to daily living activity easily this is due to limited mobility due to nerve damage experienced by post-stroke patients. To improve daily living activities, post-stroke patients need rehabilitation. Nursing actions in improving the ability of daily activities is Range of Motion (ROM) and warm compresses. This study aims to determine the effect of the combination of ROM and warm compresses on increasing daily activities in post-stroke patients in the work area of Limo District Public Health Center, Depok. The research method used is pre-experiment with a pre-post test one-group design. The technique used is purposive sampling in accordance with the inclusion criteria 50 respondents. This study was conducted for 6 days with a frequency of 1 time a day. The Barthel Index (BI) questionnaire is used to measure the ability of daily living activities. The results of the study are based on the Wilcoxon Sign Daily living activity ability test before and after the intervention (p value = 0.000 < 0.05). Therefore, it can be concluded that there is an effect of the combination of ROM and warm compresses on increasing the ability of daily living activities in post-stroke patienta.